IMPLEMENTASI HADIS-HADIS SABAR DALAM MENGHADAPI BENCANA (Studi Kasus Bencana Banjir di Kepatihan Jember) - Irfan Yuhadi; Nurul Budi Murtini (Al-Majaalis : Jurnal Dirasat Islamiyah, 2021)
In human life, it always revolves between happiness and sadness, ease and difficulty, even life and death. All the calamities that occur have been determined by Allah in the Lawh al-Mahfuz. Not a single disaster befell someone except with the permission of Allah. Allah will give guidance to the heart of believers to be patient in accepting calamities. Jember Regency consists of 226 villages, 22 subdistricts, and 31 districts, among which is Kepatihan subdistrict. In February 2021, there were floods in Jember, among the areas affected was Kepatihan. The purpose of this research is to analyze and to find the redaction of hadiths about patience, the phenomenon of the flood in Kepatihan Jember, and the implementation of the hadiths about patience in dealing with floods in Kepatihan Jember. The approach in this research is a qualitative approach with a type of case studies. The results of this study indicate that: (1) There are several redactions of hadith about patience, among them are: hadith from Abu Malik Al-Asy'ari, hadith from Anas, hadith from 'Ubadah bin Ash-Shamit, hadith from Abu Sa'id Al-Khudri, and hadith from Shuhaib – may Allah be pleased with them. (2) In Kepatihan Jember, 32 families were affected by the flood, among the worst were 8 houses. (3) The residents of Kepatihan Jember have implemented the hadiths of patience in facing the flood disaster that occurred in February 2021.